Thermal-energy characterization of a 3.3 kwp photovoltaic system interconnected to the electricity grid: 2015-2019 - Polo Bravo, Carlos (2021)
The thermal and energetic results obtained under monitoring of a 3,3 KWp photovoltaic solar system interconnected to the electrical grid of the Faculty of Sciences of the Jorge Basadre Grohmann National University of Tacna (UNJBG), Peru are presented; located at a southern latitude of 17,35 °, longitude 72 ° W and height of 525 meters above sea level in the period 2015-2019. The system generates electrical energy at 340 V DC, which with an inverter transforms it to 220 VAC, 60 Hz which is delivered to the electricity grid of the University City. The photovoltaic system is made up of twelve panels of 275 Wp and 1,65 m 2 each, oriented to the north with a south inclination of 19,5 °, zero azimuth and installed under an architecture that allows the temperature to be automatically monitored and recorded every 15 seconds of the panel, environment and solar irradiance on the plane of the panels, electrical parameters in direct (DC) and alternating (AC) voltage, during one year the data available is 365 files of 5760 rows x 16 columns, characterized under the meteorological conditions of the city of Tacna. The system is connected to the Internet, so that the data can be monitored and transferred from anywhere that has the resource. For the period January 2015 to December 2019, it has generated 25670 KWh of electric energy in alternating voltage at 220 V, 60 Hz frequency, reaching its maximum energy production months between october to march of 542, whilebetween April and September decreased to a minimum value of 228 in June, representing a difference of 42,07%; which has meant for the UNJBG a savings in electrical energy consumption of $ 779 per year. The average annualized efficiency of the system is 13,75%. The temperature of the modules in monthly interannual average varies between maximum values ​​of 42,9 ° C and minimum of 28,6° C, while the maximum instantaneous values ​​of the panel surface of 51,3 ° C in January (summer) and the minimum of 41,8 ° C in June (winter), for maximum environmental temperature changes between 30,1 and 20,5 ° C, respectively.